2010
DOI: 10.1038/ng.725
|View full text |Cite
|
Sign up to set email alerts
|

CEP152 is a genome maintenance protein disrupted in Seckel syndrome

Abstract: These authors contributed equally to this work. AUTHOR CONTRIBUTIONS The project was conceived and the experiments were planned by E.K. and B.W. We would like to note that Y.A. and K.E.B. had a comparable contribution to this study. The review of phenotypes and the sample collection were performed by B

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
225
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(232 citation statements)
references
References 15 publications
4
225
1
2
Order By: Relevance
“…In contrast to other microcephaly or Seckel cells that display numerically aberrant centrosomes, cells in the current study displayed correct numbers of centrosomes and mitotic spindle poles (Fig 1A; Rauch et al , 2008; Kalay et al , 2011; Hussain et al , 2012; Martin et al , 2014). However, interphase centrosomes displayed faint or no CPAP immunoreactivity.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…In contrast to other microcephaly or Seckel cells that display numerically aberrant centrosomes, cells in the current study displayed correct numbers of centrosomes and mitotic spindle poles (Fig 1A; Rauch et al , 2008; Kalay et al , 2011; Hussain et al , 2012; Martin et al , 2014). However, interphase centrosomes displayed faint or no CPAP immunoreactivity.…”
Section: Resultscontrasting
confidence: 57%
“…Mutations in centrosomal proteins cause developmental disorders such as primary microcephaly and Seckel syndrome (Thornton & Woods, 2009; Kalay et al , 2011; McIntyre et al , 2012; Lancaster et al , 2013; Alcantara & O'Driscoll, 2014; Bazzi & Anderson, 2014; Insolera et al , 2014; Martin et al , 2014). Microcephaly is a neurodevelopmental disorder leading to extreme reduction in brain size.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, CPAP and CEP152 are mutated in both MCPH and Seckel syndrome, suggesting that the two disorders might represent different ends of a disease continuum [26,100,102,144]. Indeed, recent reports uncovered mutations in the Seckel genes ATR and CtIP that cause primary microcephaly without PD, whereas short stature has been noted in some individuals with mutations in the MCPH gene, CDK5RAP2 [16,89,145].…”
Section: Perspectivesmentioning
confidence: 99%
“…If inactivation or clustering is efficient, cells can survive but at a cost; centrosome clustering causes not only mitotic delay, but also chromosomal instability [55,61]. Importantly, genome instability has been documented in CPAP-Seckel mouse and in Seckel patient-derived cells; CEP152-Seckel lymphocytes exhibit aneuploidy in addition to abnormal mitotic spindle morphologies [100,101].…”
Section: Centrosomes and Body Size (A) Primordial Dwarfism Syndromesmentioning
confidence: 99%
“…Genetic analysis has demonstrated that the biological roles of centrioles differ widely among organisms: Caenorhabditis elegans embryos without centrioles arrest at the two-cell stage, whereas zygotic removal of centrioles in Drosophila allows survival to adult stages (3)(4)(5). In humans, mutations in centriolar and centrosomal proteins are associated with microcephaly or microcephaly in the context of dwarfism (6)(7)(8)(9)(10). Abnormal numbers of centrioles are associated with cancer, although it is not clear whether abnormal centrosome number is a cause or an effect of tumorigenesis (1,(11)(12)(13).…”
mentioning
confidence: 99%